Modelagem de um veículo elétrico de alcance estendido (REEV) utilizando um motor de ignição por compressão de carga homogênea (HCCI) a etanol - Sousa, Renno de Holanda (2024)
This study analyzed the behavior of different configurations of a REEV, adopting two distinct power sets fueled by ethanol: one operating as a spark-ignition engine and the other in HCCI mode. The simulations were performed in Realis IGNITE software, and the emissions treatment was conducted by a Python program. The computational model of the conventional vehicle showed satisfactory results in fuel consumption, with less than 1% validation error, while the three-way catalyst model had a maximum error of less than 3%. The results obtained with the power set operating in HCCI mode were also satisfactory, showing superior performance to the other configuration, with lower fuel consumption and pollutant emissions within the limits reported in the literature.